PENGARUH KOMUNIKASI, KONFLIK, DAN STRESS KERJA TERHADAP PRODUKTIVITAS KARYAWAN PT SUMIYATI EKSPORT IMPORT INTERNASIONAL (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2022)
The purpose of this study was to determine the Communication, Conflict and Work Stress partially (alone) and simultaneously (together) on the Productivity of PT Sumiyati Export Import International Employees in Yogyakarta City. The research was conducted by distributing questionnaires, while the research method was using Simple Random Sampling. The independent variables in this study are communication, conflict and work stress. On the other hand, the dependent variable in this study is Employee Productivity of PT Sumiyati Export Import International in Yogyakarta City. The data collection method was used by distributing questionnaires directly to employees of PT Sumiyati Export Import International with a total of 80 Employees. The analytical method used in this research is the analysis of the coefficient of determination, the multiple regression analysis of the F test and the t test, using SPSS Version 25.00. The t test shows that communication, conflict and work stress partially (alone) have a positive relationship and significantly affect the productivity of PT Sumiyati Export Import International employees in the city of Yogyakarta and there is a simultaneous (together) effect between work stress, conflict and communication on employee productivity at PT Sumiyati Export Import International in Yogyakarta City. The adjusted R2 value is 88.8, % of the contribution of communication variables, conflict and work stress to the productivity of PT Sumiyati Export Import International Yogyakarta City employees and the remaining 15.6% is explained by other factors.